POLYMERIC MICELLES: POTENTIAL DRUG DELIVERY DEVICES - Deepak, Payal; Nagaich, Upendra; Sharma, Aman; Gulati, Neha; Chaudhary, Amit (Indonesian Journal of Pharmacy, 2013)
Polymeric micelles (PMs) have been the most popular and promising topic of many researches in the field of drug delivery and targeting for the past two decades. Polymeric micelles are the selfassembled nano-sized colloidal particles which are made up of amphiphilic block copolymers i.e. polymers consisting of hydrophobic block and hydrophilic block. In this highlight, we give an overview of the structure of micelles and polymeric micelles followed by a summary of the methods used for their preparation. We then focus on several kinds of PMs based on intermolecular forces such as polyion complex micelles (PICMs), non-covalently connected micelles (NCCMs) and recently developed smart polymeric assemblies which can respond to the application of external stimuli such as a change in temperature, pH, redox and light to afford novel nanomaterials. The types of polymers used in the preparation of PMs have also been highlighted so as to facilitate its use in drug delivery and targeting. These polymeric micelles nanocarriers have applications in drug delivery primarily such as anticancer therapy, to the brain to treat neurodegenerative diseases, antifungal agents, stimuli-responsive nanocarriers for drug and gene delivery, ocular drug delivery. Targeted drugs will hopefully reduce adverse reactions by limiting their action to cancer tissue only. Finally, this review broadly presents the basic aspects of PMs which help in delivery and targeting of actives with its recent advancements and applications.Key words: micelles, polymeric micelles, block copolymer, stimuli sensitivity